Evolution of Political Risk Concept: Classical and Contemporary Interpretations - D. A. Nechkin (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Political risk analysis emerged as a distinctive field within applied international studies at the height of the Cold War but recently it has received a new impetus. It was preconditioned by an increasing uncertainty in many segments of world politics after a series of powerful ‘strategic shocks’ (‘Arab Awakening’, ‘Ukrainian crisis’, Brexit etc.) which brought about substantial and often completely unforeseen, direct and indirect consequences for the international business activities all over the world. This paper examines both classical approaches to defining political risk, which were elaborated by the leading experts in this field in the 1970–1980s, and its contemporary interpretations proposed in academic literature, and reports of think tanks and consultancies over the last decade. The author outlines a new classification of the main definitions of political risks, based on the factors that affect a company, be it the host government’s actions, sanctions or a general destabilization of the business environment as a result of certain political events. The paper identifies the key drivers behind the development of contemporary approaches to defining political risks, including an increasing influence of non-governmental actors, destabilizing processes in certain developed countries, etc. The author shows that these factors have broadened the concept by reinterpreting what generates political risks, in what circumstances and what impact they have on a risk bearer (a foreign company).